Tackling challenges of global health electives: Resident experiences of a structured and supervised medicine elective within an existing global health partnership - Tubman, Michelle; Maskalyk, James; MacKinnon, David; Venugopal, Raghu; Fremes, Elayna; Puchalski Ritchie, Lisa; Azazh, Aklilu; Landes, Megan (Canadian Medical Education Journal, 2017)
Background: The Toronto-Addis Ababa Academic Collaboration in Emergency Medicine (TAAAC-EM) deploys teaching teams of Canadian EM faculty to Addis Ababa to deliver a longitudinal residency curriculum. Canadian trainees participate in these teams as a formally structured and supervised elective in global health (GH) and EM, which has been designed to enhance the strength of GH electives and address key challenges highlighted in the literature. Methods: The purpose of this qualitative study was to identify, describe, and evaluate strengths and weaknesses of this elective in relation to its purposeful structure. Residents who completed the elective were invited to participate in face-to-face interviews to discuss their experiences. Results: The findings show that the residents both chose this elective because of its purposefully designed features, and that these same features increased their enjoyment and the educational benefit of the elective. Supervised bedside teaching, relationships shared with Ethiopian residents, and the positive impact the experience had on their clinical practice in Canada were identified as the primary strengths Conclusion: Purposeful and thoughtful design of global health electives can enhance the resident learning experience and mitigate challenges for trainees seeking global health training opportunities.